Modelling a sub-10 second 100m sprinter using Newton's equations of motion - Richmond, J. (New Studies in Athletics, 2011)
After the exploits of Usain Bolt in 2008 and 2009, many have asked: how it is possible that a human could run so fast? For rivals seeking to close the gap, strength training, the central element of the modern training paradigm for sprinters, offers only limited proven benefits for increasing maximal running velocity, which is the apparent key to Bolt`s domination.